Boost your English proficiency - The Star, (2012)
STUDENTS applying for Universiti Putra Malaysia's (UPM) undergraduate and postgraduate programmes can now take up the Certified Intensive English Programme (CIEP)from ELS Language Centres (ELS),which is recognised as proof of sufficient English language proficiency for admissions.